Newspaper Row, 236-248 Washington Street, 1885-95 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking north of multi-story buildings on the right side of the Washington Street. A few people on on the sidewalk. Some buildings have awnings on the upper floors that are retracted. 13 3/8 x 7 1/2 overall 13 13/16 x 7 13/16 Photographs